The influence of Fe2O3 reagent grade purity on the electrical properties of 'undoped' LaFeO3 ceramics: A cautionary reminder. Issue 7 (July 2021) - Li, Linhao; Walkley, Brant; Reaney, Ian M.; Sinclair, Derek C.
Abstract: Low levels of impurities can have a dramatic influence on the electrical properties of metal oxides. Here, we use a combination of impedance spectroscopy and Seebeck coefficient measurements to show the defect chemistry and p-type conduction mechanism in undoped LaFeO3 (LF) ceramics is significantly influenced by impurities in Fe2 O3 reagents. A low but significant concentration of impurities associated with 99.9 % Fe2 O3 reagent is sufficient to compete against the intrinsic Schottky disorder responsible for the p-type behaviour normally observed for undoped LF ceramics. This produces electrically heterogeneous grain (bulk) responses that are strongly dependent on the processing conditions. To achieve electrically homogeneous bulk responses requires adjustment of the oxygen content by annealing in a reducing atmosphere (n-type) or via doping with a significant level of acceptors (mixed ionic/ p-type electronic). These results illustrate the importance of using high purity reagents when studying the electrical properties of ferrite-based perovskites.